Human Vγ9Vδ2 T cells: Innate adaptors of the immune system - Doherty, Derek (My University, 2015)
Unconventional T cells are gaining center stage as important effector and regulatory cells that orchestrate innate and adaptive immune responses. Human Vc9/Vd2 T cells are amongst the best understood unconventional T cells, as they are easily accessible in peripheral blood, can readily be expanded and manipulated in vitro, respond to microbial infections in vivo and can be exploited for novel tumor immunotherapies. We here review findings that suggest that Vc9/Vd2 T cells, and possibly other unconventional human T cells, play an important role in bridging innate and adaptive immunity by promoting the activation and differentiation of various types of antigen-presenting cells (APCs) and even turning into APCs themselves, and thereby pave the way for antigen-specific effector responses and long-term immunological memory. Although the direct physiological relevance for most of these mechanisms still needs to be demonstrated in vivo, these findings may have implications for novel therapies, diagnostic tests and vaccines
PUBLISHED
Keywords: human T cells; human T cells